Simultaneous improvement in strength and plasticity of Ti-24Nb-4Zr-8Sn manufactured by selective laser melting. (5th November 2018) - Yang, C.L.; Zhang, Z.J.; Li, S.J.; Liu, Y.J.; Sercombe, T.B.; Hou, W.T.; Zhang, P.; Zhu, Y.K.; Hao, Y.L.; Zhang, Z.F.; Yang, R.
Abstract: The strength and plasticity of metallic materials usually exhibit a trade-off relation. This study reports a simultaneous improvement in the ultimate tensile strength (UTS) and uniform elongation (UE) of Ti-24Nb-4Zr-8Sn (Ti2448) fabricated by selective laser melting (SLM), relative to those produced via forging. Detailed microstructural characterization reveals that the outstanding tensile property may result from the bi-model structure that forms during the rapid cooling associated with SLM. Coarse grains are surrounded by fine grains within the melt pool, which causes a back stress during tension. The back stress provides additional strain-hardening capacity, which postpones the initiation of necking and then leads to the simultaneous improvement of the strength and plasticity (SISP) of the Ti2448 alloy. Furthermore, the tensile property of the SLM-fabricated sample is anisotropic which is strongly related to the irregular shape of the melt pool. Graphical abstract: Unlabelled Image Highlights: Melt pools with a bi-model structure are formed in a biocompatible Ti alloy through selective laser melting. The as-built Ti alloy exhibits a better combination of strength and plasticity, relative to traditionally forged counterpart. For the first time, the back stress of the melt pool along different directions is studied through finite element modelling.